Productivity of Forages in Grassland Merapi Post-Eruption Area,Sleman, Yogyakarta, Indonesia - Umami, Nafiatul; Suhartanto, Bambang; Suwignyo, Bambang; Suseno, Nilo; Fenila, Sarah A.; Fajarwati, Ruslina (Universitas Jendral Soedirman, 2015)
This research was aimed to investigate the productivity and quality of forages (including dry matter, organic matter, crude fiber, crude protein, and extract ether) in the area of Kali Kuning and Krasak River. This area was affected by Mount Merapi Eruption on 2010. The data were taken from the area around the river that was firstly revegetated after the eruption. The forage classified as grass, legume and forbs. The method applied in the research was Line Intercept method by observing the botanical composition there at several observation points. The forage was taken as the sample, then calculated the production, and proximately analyzed to determine its chemical composition. The results showed that around the river, the widest cover area in 2013 and 2014 was Brachiaria brizantha grasses. The highest dry matter in 2013 and 2014 was 165.57 gm–2 in Pennisetum purpuphoides and 190.37 gm–2 in Brachiaria brizantha, respectively. Forbs with another type of weed also spread in this area. The quality of forages around Krasak River increased in 2014 due to the addition of organic matter contained in the soil and the minerals weathering from year to year